CO2 EMISSIONS AND IMMIGRATION IN THAILAND: NEW EVIDENCE FROM BOOTSTRAP ARDL APPROACH - John Smith; Sirinya Siriyanun5; Mohd Faizal Azrul Azwan Muhamed Che Harun; Muhammad Zainuddin Mohamed Azudin; Nur Fakhzan Marwan; Azyyati Anuar; Arshian Sharif (Journal of Islamic, Social, Economics and Development, 2023)
Immigration in general is believed to have a negative impact on natural resources. Despite this, researchers have rarely addressed the relationship between immigration and climate change, thus this study attempts to fill in the gap by investigating the dynamic linkages among CO2 emissions, economic growth, immigration, energy consumption and financial development in the context of the EKC hypothesis for Thailand, incorporating the structural breaks over the period of 1997-2019 using Bootstrap ARDL bound cointegration. It is found that all explanatory variables positively and significantly affect CO2 emissions in both the short run and the long run. Furthermore, the validity of the EKC hypothesis is confirmed in the long run but is invalid in the short run. Nevertheless, over time, immigrants contribute less to CO2 emissions, perhaps owing to the Thailand’s tighter rules and regulations implemented in preserving the environment. This proves that with proper implementation of mitigation strategies and practices, immigration can significantly help in reducing CO2 emissions.